Pengaruh Literasi Keuangan Dan Sikap Keuangan Terhadap Perilaku Pengelolaan Keuangan Pada Pelaku UMKM Kuliner Di Kelurahan Karawang Kulon - Makmur, Ayang Maubi Yuliani; Isyanti, Puji; Sumarni, Neni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The very rapid development of MSMEs still has various problemsor obstacles in business development which can be seen from theability in financial management behavior in MSMEs. Not allbusiness actors know about the knowledge of financial managementof the business they are working on or carrying out. The problem often faced by MSMEs in Karawang Kulon is limitations in managing finances. This research aims to determine and analyzethe influence of financial literacy and financial attitude variableson financial management behavior among Culinary MSMEs in Karawang Kulon District, both partially and simultaneously. The methodology used in this research is a quantitative method and usesmultiple linear regression analysis tools using the SPSS version 25 program. The results of this study explain that there is a partialinfluence of financial literacy on financial management behavior, financial attitudes on financial management behavior and there is a simultaneous influence Financial literacy and financial attitudestowards financial management behavior among culinary MSMEs in Karawang Kulon.